Correction: Advance Care Planning in Dementia: Do Family Carers Know the Treatment Preferences of People with Early Dementia? - Karen Harrison Dening; Michael King; Louise Jones; Victoria Vickerstaff; Elizabeth L Sampson (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0159056.].